Pengaruh Customer Experience, Ease Of Use, Dan Customer Trust Terhadap Repurcase Intention Konsumen Pada Online Shop Shopee (Studi Kasus Pada Santri Pesantren Kampus Ainul Yaqin Unisma) - Luluk Fitria; Rois Arifin; Aleria Irma Hatneny (UNIVERSITAS ISLAM MALANG, 2021)
ABSTRAKThis research was conducted with the aim of analyzing the variables of Customer Experience, Ease of Use and Customer Trust towards Repurcase Intention at the Shopee online shop at the Santri Pesantren Campus Ainul Yaqin Unisma. This research uses explanatory research with descriptive and quantitative approaches. The population in this study were students of Ainul Yaqin Unisma Jln. Tata Surya, Lowokwaru sub-district, Dinoyo, Malang online shop user Shopee.co.id. The sampling technique used was purposive sampling assisted by the Slovin formula, so the research sample was obtained as many as 67 respondents. Data were analyzed using multiple linear regression analysis processed with SPSS 25.0 software. The data collection method used was a questionnaire. The results showed that the variables of Customer Experience, Ease of Use and Customer Trust had a significant effect simultaneously on Repurcase Intention. Customer Experience and Customer Trust variables have a partially significant effect on Repurcase Intention, while the Ease of Use variable does not have a partial significant effect on Repurcase Intention.Keywords: Customer Experience, Ease Of Use, Customer Trust, Repurcase Intention